Experiences and life circumstances of unintentionally pregnant women affected by intimate partner violence—stress factors, resources, healthcare structures and needs: a scoping review protocol - Kristina Winter; Kristina Winter; Jana Niemann; Jana Niemann; Dennis Jepsen; Petra J. Brzank (Frontiers in Public Health)
This scoping review outlines the current understanding, challenges, available resources, and healthcare needs of women affected by intimate partner violence (IPV) who experience unintended pregnancy (UP). UPs are defined as unwanted, unplanned, or mistimed pregnancies. The impact of UP is multifaceted and carries several additional risks, particularly for women who experience IPV. The experiences and living conditions, including (mental) burdens, resources, care structures, and the needs of unintentionally pregnant women who have experienced IPV, remain mostly unexplored. The review will include the following criteria: (i) reproductive-aged women who have experienced IPV and UP; (ii) publications that provide detailed accounts of the experiences, circumstances, and/or needs of women with UP who have experienced IPV. This study will utilize the JBI methodology for scoping reviews and follow the PRISMA Protocol for Scoping Reviews (PRISMA-ScR). A total of 2,325 papers and gray literature published from 2000 to the present were identified. 1,539 literature items were included in the title and abstract screening. Two researchers will independently choose studies, perform data extraction, and perform data synthesis. Quantitative data will be narratively summarized and qualitative data will be analyzed using thematic analysis. The findings will identify research gaps and provide insights into an important topic of reproductive healthcare and the (mental) health situation of a particularly vulnerable group. This will be useful in defining indications for researchers, professionals, and policymakers in public, mental, and reproductive health to conceptualize interdisciplinary and empirical healthcare support for affected women.Systematic review registrationOpen Science Framework: https://doi.org/10.17605/OSF.IO/ZMVPE.